Assessing Vegetation Cover Changes in the Eastern and Western Regions of the Tigris River Using GIS and Remote Sensing - Musa, Maryam Basim; Albakry, Sundus A. Abdullah; Sultan, Maitham A. (Iraqi Journal of Science, 2025)
Monitoring vegetation change is essential to monitoring natural and human factors affecting vegetation area and land use. The research aims to detect the change in vegetation cover during 2008, 2010, 2013, 2015, 2018, 2019, and 2023 in the eastern and western parts of the Tigris River in Baghdad, Iraq. Landsat 5 (Thematic Mapper) and 8 (Operational Land) satellite images were used. They were classified using the NDVI index (Normalized Difference Vegetation Index) to detect changes in vegetation and the NBI index (New Urbanism Index) to detect urban expansion using ArcMap 10.8. The results showed that the largest vegetation cover area was 77.69 km2 in 2013, followed by 2023, which was 68.58 km2; then, in 2018, it was 68.36 km2. In 2008, 2010, 2015, and 2019, there was a significant decrease in the vegetation cover areas, reaching 61.92 km2 in 2008, 60.62 km2 in 2010, 46.14 km2 in 2015, and 46.04 km2 in 2019. The vegetation cover area decreased from 77.69 km2 in 2013 to 46.14 km2 in 2015 due to the decrease in annual rainfall rates from 296.7 mm to 190.9 mm. In addition, there was a significant increase in building areas for 2008-2023 from 156.26 km2 to 173.5 km2 due to the increased population density and urban expansion in Baghdad. Because plants are the home of living organisms, reducing green spaces threatens biodiversity and poses health risks, as plants contribute to purifying the air.